Together, alone? Performance, protest and digital proximities in India's Blank Noise feminist campaign. Issue 3 (2nd September 2019) - Savory Fuller, Rebecca
ABSTRACT: This article examines the performative digital practices of India's feminist campaign group Blank Noise, with a focus on their 2016 project #WalkAlone. The event sought to explore and challenge embodied notions of female safety and visibility in night-time urban public spaces, by inviting women to walk alone in a place of their choosing between 9pm and midnight. In doing so, Blank Noise called on participants to 'walk alone, together', utilising digital documentation tools and media platforms to network these dispersed embodied acts. Drawing on my participation in #WalkAlone from the remote position of the UK alongside online documentation of the project, I examine how these tools established 'digital proximities' between participants, transforming our solitary acts into collective embodied action. I argue that Blank Noise's project extends Butler's notion of 'plural performativity' (2015) into a digital public sphere, by constructing a mode of embodied assembly within media spaces. Here, digital proximities between dispersed participants forged a concerted enactment from the private and personal actions of individual women, walking on the stage of the nocturnal city.